Role of Noradrenergic Inputs From Locus Coeruleus on Changes Induced on Axotomized Motoneurons by Physical Exercise - Arbat-Plana, Ariadna; Puigdomenech, Maria; Navarro, Xavier; Udina, Esther (Frontiers in Cellular Neuroscience, 2019)
Physical rehabilitation is one of the cornerstones for the treatment of lesions of the nerv-ous system. After peripheral nerve injuries, activity dependent therapies promote trophic support for the paralyzed muscles, enhance axonal growth and also modulate the maladaptive plastic changes induced by the injury at the spinal level. We have previously demonstrated that an in-tensive protocol of treadmill running in rats reduces synaptic stripping on axotomized motoneu-rons, preserves their perineuronal nets and attenuates microglia reactivity. However, it is not clear through which mechanisms exercise is exerting these effects. Here we aimed to evaluate if activation of the locus coeruleus (LC), the noradrenergic center in the brain stem, plays a role in these effects. Since LC is strongly activated during stressful situations, as during intensive exer-cise, we selectively destroyed the LC by administering the neurotoxin DPS-4 before injuring the sciatic nerve of adult rats. Animals withouth LC had increased microglia reactivity around in-jured motoneurons. In these animals, an increasing intensity protocol of treadmill running was not able to prevent synaptic stripping on axotomized motoneurons and the reduction in the thick-ness of their perineuronal nets. In contrast, treadmill running was still able to attenuate microglia reactivity DSP-4 treated animals, thus indicating that the noradrenergic projections are important for some but not all the effects that exercise induces on the spinal cord after peripheral nerve injury. Moreover, animals subjected to treadmill training showed delayed muscle reinnervation, more evident if treated with DSP-4. However, we did not find differences in treated animals re-garding the H/M amplitude ratio, which increased during the first stages of regeneration in all injured groups.